Full-length synaptonemal complex grows continuously during meiotic prophase in budding yeast. - Karen Voelkel-Meiman; Sarah S Moustafa; Philippe Lefrançois; Anne M Villeneuve; Amy J MacQueen (PLoS Genetics, 2012)
the synaptonemal complex (SC) links two meiotic prophase chromosomal events: homolog pairing and crossover recombination. SC formation involves the multimeric assembly of coiled-coil proteins (Zip1 in budding yeast) at the interface of aligned homologous chromosomes. However, SC assembly is indifferent to homology and thus is normally regulated such that it occurs only subsequent to homology recognition. Assembled SC structurally interfaces with and influences the level and distribution of interhomolog crossover recombination events. Despite its involvement in dynamic chromosome behaviors such as homolog pairing and recombination, the extent to which SC, once installed, acts as an irreversible tether or maintains the capacity to remodel is not clear. Experiments presented here reveal insight into the dynamics of the full-length SC in budding yeast meiotic cells. We demonstrate that Zip1 continually incorporates into previously assembled synaptonemal complex during meiotic prophase. Moreover, post-synapsis Zip1 incorporation is sufficient to rescue the sporulation defect triggered by SCs built with a mutant version of Zip1, Zip1-4LA. Post-synapsis Zip1 incorporation occurs initially with a non-uniform spatial distribution, predominantly associated with Zip3, a component of the synapsis initiation complex that is presumed to mark a subset of crossover sites. A non-uniform dynamic architecture of the SC is observed independently of (i) synapsis initiation components, (ii) the Pch2 and Pph3 proteins that have been linked to Zip1 regulation, and (iii) the presence of a homolog. Finally, the rate of SC assembly and SC central region size increase in proportion to Zip1 copy number; this and other observations suggest that Zip1 does not exit the SC structure to the same extent that it enters. Our observations suggest that, after full-length assembly, SC central region exhibits little global turnover but maintains differential assembly dynamics at sites whose distribution is patterned by a recombination landscape.